An assessment of the knowledge, attitude and practices on hand hygiene among medical undergraduates at Chamarajanagar, Karnataka: A questionnaire- based study - Trupti B. Naik; Meghana B.M; Vijaykumar Mane; Asmabegaum Biradar (Al Ameen Medical College, 2023)
Background: Hand hygiene is one of the simplest and the most important cost-effective measures in the prevention of Hospital-acquired infections (HAIs). HAIs result in high morbidity and mortality besides additional costs. On the other hand, compliance rates of hand hygiene among health-care workers, remains low. Objective: To estimate the level of knowledge, attitude, and practices on Hand hygiene among medical undergraduates in the study setting. Materials and Methods: A cross-sectional study was conducted among 535 medical undergraduates for duration of 6 months from January 2021 to June2021 at a government medical college in Chamarajanagar, Karnataka. Data was collected using a pre-tested, semi-structured questionnaire, and statistical analysis was performed with WHO Epi info software version 3.5.4. Results: The proportion of students having a satisfactory level of knowledge, attitude, and practices were 512 (95.70%), 447 (83.55%), and 356 (66.54%) respectively and the difference among them was statistically significant. Conclusion: The present study finds the Knowledge, Attitude, and Practices (KAP) gap among medical students, emphasizing the need for behaviour change communication for the same.